Market Mavenism: Its Contribution in Building Consumerâs Trust - Puspa, Jofi; Rahardja, Conny Tjandra (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
In globalization era, firms have to deal with multifaceted challenges. Dynamic changes in consumersâ demands and desires, technology, and new knowledge and innovative movement of competitors are some examples of the important tasks to be managed in order to be able to survive in the market. The role of communications and the presence of market maven cannot be ignored because both are salient elements for establishing a firmâs marketing strategy. Market maven has been well defined and studied. However, the participation of market maven in improving a consumerâs knowledge and trust in certain object is unclear. Therefore, this study aims to: (1) investigate the role of inherent personal knowledge in affecting trust, (2) investigate as to whether mavens play a role in improving a recipientâs knowledge level and trust. The authors conducted a study that involved a total of 134 students as respondents. The correlation between subjective knowledge and trust attains a medium level, while objective knowledge is related to trust at a very low level. Trust in the low maven group is the lowest compared to that in medium and high mavens. This study indicates that there are different results in terms of effects of information provided by three different maven groups.